2004
DOI: 10.4049/jimmunol.173.5.3193
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Inhibits IL-2 Production by Preventing Protein Kinase C-Dependent NF-κB Activation: Possible Role in Protein Kinase Cθ Regulation

Abstract: The role of the sphingolipid ceramide in modulating the immune response has been controversial, in part because of conflicting data regarding its ability to regulate the transcription factor NF-κB. To help clarify this role, we investigated the effects of ceramide on IL-2, a central NF-κB target. We found that ceramide inhibited protein kinase C (PKC)-mediated activation of NF-κB. Ceramide was found to significantly reduce the kinase activity of PKCθ as well as PKCα, the critical PKC isozymes involved in TCR-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
27
0
1
Order By: Relevance
“…The signalling of Toll-like receptors TLR3-7/8 is disrupted by exogenous addition of βDGalp (1)(2)(3) [39]. The exogenous addition of ceramide inhibits protein kinase C-mediated activation of NF-κB [40].…”
Section: Discussionmentioning
confidence: 99%
“…The signalling of Toll-like receptors TLR3-7/8 is disrupted by exogenous addition of βDGalp (1)(2)(3) [39]. The exogenous addition of ceramide inhibits protein kinase C-mediated activation of NF-κB [40].…”
Section: Discussionmentioning
confidence: 99%
“…피부장벽의 손상은 외인성 알레르겐에 대해 장벽으로 . 각질층의 손상은 sphingosine을 생성시키며, 생성된 sphingosine이 protein kinase C (PKC)의 활성을 증가시 킨다 20) . 활성화된 PKC는 피부 상피 기저층에서 IL-4와 같은 Th2 사이토카인의 활성을 야기한다고 보고된바 …”
Section: Ae군의 피부 대부분에서 각질층이 손상된 습진 (Eczema)이 나타났으며 일부 가장자리지역에서는 탈락 과unclassified
“…6C). Next, we utilized a PKC inhibitor, C6-ceramide (45). Jurkat cells were pretreated with C6-ceramide (10 M) for 30 min at 37°C before heat shock, and the results showed that C6-ceramide impaired accumulation of PKC, IKK␣, and IKK␤ as well as the NF-B-IB␣ complex into the lipid rafts (fraction 5) in response to heat stress (Fig.…”
Section: Membrane Lipid Raft Recruitment Of Pkc During Hyperthermiamentioning
confidence: 99%